DEPENDENCE OF YIELD AND SOWING QUALITIES OF WINTER RAPE SEEDS ON VARIETY AND CULTIVATION TECHNOLOGY IN THE CONDITIONS OF THE RIGHT-BANK FORESTSTEPPE OF UKRAINE - Savchuk, Yu. M.; Antonenko, A. F. (Scientific Progress & Innovations, 2019)
Rape occupies a leading place among crops, because it is one of the most profitable, as a result of which the interest of agrarians in growing it increases. That is why it is necessary to optimize the traditional technology of cultivating this crop under the agro-climatic zone to obtain a better harvest. The purpose of the article is to evaluate the yield and sowing qualities of winter rape varieties’ seeds in the conditions of the Right-bank Forest-Steppe of Ukraine, depending on the variety and elements of cultivation technology. The research task was to determine the impact of varieties and micro-fertilizers on yield and crop quality of winter rape seeds, depending on the sowing time in the conditions of the Right-Bank Forest-Steppe of Ukraine. The trials were carried out during 2013–2016 on the experimental fields of the separate unit of the National University of Life and Environmental Sciences of Ukraine “Agronomic Research Station”. Laboratory studies were conducted by the Department of Genetics, Selection and Seed Growing named after Prof. M. Zelensky. Basic research methods were field and laboratory. The results of the conducted trials proved that in order to obtain high yields of winter rape varieties the optimal sowing time was August, 21 under the application of Wuxal micro-fertilizer. The highest yields and weight of 1000 seeds were recorded for Vesuviy - 3.30 t/ha and 4.4 g and Snihova Koroleva varieties – 3.51 t/ha and 4.57 g when Wuxal Microplant fertilizer was applied during the optimal sowing time. The seeds sown on August, 21, had the best sowing qualities. The highest germination rate was detected in Vesuviy under applying Wuxal Microplant microfertilizer – 90.1 % and Snihova Koroleva varieties under applying Wuxal Microplant and Terios micro-fertilizers – 90.3 and 90.6 %, respectively. Laboratory germination capacity of seeds was higher in Vesuviy variety; under the optimal sowing time and the effect of Wuxal Terios and Askofol micro-fertilizers it was 98.8 and 98.6 %, respectively. Concerning Snihova Koroleva variety, the highest index was 99.7 % under the application of Wuxal Microplant micro-fertilizer in the optimal sowing time. The yield of certified seeds was the best when sowing Snihova Koroleva variety on August, 21 under Wuxal Microplant application – 85.4 %. So, to obtain better yield and sowing qualities of winter rape varieties’ seeds under the conditions of the Right-Bank Forest- Steppe of Ukraine the optimal sowing time is to be August, 21 under the application of Wuxal Microplant and Terios micro-nutrients.